MYB103 is required for FERULATE‐5‐HYDROXYLASE expression and syringyl lignin biosynthesis in Arabidopsis stems. (19th October 2012) - Öhman, David; Demedts, Brecht; Kumar, Manoj; Gerber, Lorenz; Gorzsás, András; Goeminne, Geert; Hedenström, Mattias; Ellis, Brian; Boerjan, Wout; Sundberg, Björn
Summary The transcription factor MYB103 was previously identified as a member of the transcriptional network regulating secondary wall biosynthesis in xylem tissues of Arabidopsis, and was proposed to act on cellulose biosynthesis. It is a direct transcriptional target of the transcription factor SECONDARY WALL ASSOCIATED NAC DOMAIN PROTEIN 1 (SND1), and 35S‐driven dominant repression or over‐expression of MYB103 modifies secondary wall thickness. We identified two myb103 T‐DNA insertion mutants and chemically characterized their lignocellulose by pyrolysis/GC/MS, 2D NMR, FT‐IR microspectroscopy and wet chemistry. The mutants developed normally but exhibited a 70–75% decrease in syringyl (S) lignin. The level of guaiacyl (G) lignin was co‐ordinately increased, so that total Klason lignin was not affected. The transcript abundance of FERULATE‐5‐HYDROXYLASE (F5H), the key gene in biosynthesis of S lignin, was strongly decreased in the myb103 mutants, and the metabolomes of the myb103 mutant and an F5H null mutant were very similar. Other than modification of the lignin S to G ratio, there were only very minor changes in the composition of secondary cell‐wall polymers in the inflorescence stem. In conclusion, we demonstrate that F5H expression and hence biosynthesis of S lignin are dependent on MYB103.